2007
DOI: 10.1016/j.apsusc.2006.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Ordered nano-scale domains in lithium niobate single crystals via phase-mask assisted all-optical poling

Abstract: We report the formation of directionally-ordered nanoscale surface domains on the +z face of undoped congruent lithium niobate single crystals by using UV illumination through a phase mask of sub-micron periodicity with an energy fluence between ~90 mJ/cm 2 and 150 mJ/cm 2 at λ=266 nm. We clearly show here that the UV-induced surface ferroelectric domains only nucleate at and propagate along maxima of laser intensity. Although the domain line separation varies and is greater than 2µm for this set of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For static exposures, arrays of illuminated spots with identical exposure times, ranging from a few milliseconds to a few tens of seconds, were formed. The separation between the edges of adjacent illuminated spots in the arrays varied from 0 to 6 m which permitted us to verify if any proximity effect existed such as that observed in pulsed laser direct poling 5 where the closest approach observed there was of order ϳ2 m, irrespective of illuminated pattern resolution. For both types of exposures, the power was varied between 20-28 mW.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For static exposures, arrays of illuminated spots with identical exposure times, ranging from a few milliseconds to a few tens of seconds, were formed. The separation between the edges of adjacent illuminated spots in the arrays varied from 0 to 6 m which permitted us to verify if any proximity effect existed such as that observed in pulsed laser direct poling 5 where the closest approach observed there was of order ϳ2 m, irrespective of illuminated pattern resolution. For both types of exposures, the power was varied between 20-28 mW.…”
mentioning
confidence: 99%
“…Previous work has shown that ultraviolet ͑UV͒ and visible laser light can either directly invert 5 or assist the domain inversion process in LN. [6][7][8][9] In this paper, however, a different effect is presented whereby illumination of the +z face with UV light at = 244 nm ͑with photon energy greater than the LN band gap͒ inhibits domain inversion in illuminated areas during subsequent electric field poling ͑EFP͒.…”
mentioning
confidence: 99%
“…Although the fabrication of 3D NPCs is extremely difficult, many experimental explorations have been done. The most possible realization of the 3D NPC now seems to be the domain reversal induced by ultraviolet pulses [20,21] and femtosecond laser [22][23][24] due to the relatively convenient operation of light which avoids the complicated scheme including multiple steps such as bonding, cutting, and regrowth. Once the fabrication of the 3D NPC comes true, a great deal of work may be concentrated on this newly arisen research direction.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the trigonal crystal structure of this material favors domain formation along its three equivalent symmetry directions, resulting in a three-fold ray surface-pattern of sub-lm ferroelectric domains that do not extend through the bulk of the crystal. 10 Nevertheless, modification of the polar faces may be a valid route to control the dynamics of polarization switching.…”
mentioning
confidence: 99%